The Effect of Brand Equity toward Purchasing Decision of HP Laptop in Bengkulu City - Mustika Rahmawati; Meilaty Finthariasari (Penerbit Jurnal Indonesia, 2021)
This study aimed to determine the effect of brand equity toward purchasing decision of HP laptop in Bengkulu city. The sample of this study were 96 people. The data analysis technique of this study used simpel linier regression test and partial test. The result of this study indicate that the brand equity variabel has a significant effect toward puchasing decision of HP laptop in Bengkulu city. It states that the brand equity variable (X) has a positive and significant effect toward purchasing decision (Y). This is based on the results of the tcount> ttable that is (10.317>1.988552) and (sig < a = 0.000 < 0.050).